Preparation method and application of core-shell NH2-MIL-68-coated NH2-MIL-53 piezoelectric photocatalyst
By preparing the core-shell NH2-MIL-68@NH2-MIL-53 piezoelectric photocatalyst, the problem of low carrier separation and transmission efficiency in MOFs photocatalytic water decomposition and clean energy production is solved by using Fe3+ ion concentration regulation and piezoelectric effect, and efficient photocatalytic full water decomposition and clean energy production are achieved.
Patent Information
- Application Number
- CN202510747827.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-05
- Publication Date
- 2025-08-12
AI Technical Summary
In the photocatalytic total water-removing reaction, existing MOFs face problems such as insufficient oxidation potential of photogenerated holes, low carrier separation and transmission efficiency, which limit their hydrogen production capacity without the added sacrificial agent.
The core-shell NH2-MIL-68@NH2-MIL-53 piezoelectric photocatalyst is used to finely regulate the concentration of Fe3+ ions to prepare heterojunction structures with different shell thicknesses, and combined with the piezoelectric effect, it promotes the separation and transmission of photogenerated charge carriers.
It significantly improves the efficiency of photocatalytic water decomposition, produces efficient hydrogen and oxygen yields, demonstrates excellent catalytic activity and stability, and promotes the advancement of photocatalytic technology and the development of clean energy.
Smart Images

Figure CN120460023A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nanomaterial preparation, and specifically relates to a piezoelectric photocatalyst preparation technology of core-shell NH2-MIL-68@NH2-MIL-53 and its application in the field of piezoelectric photocatalytic complete water splitting. Background Art
[0002] As the global energy system accelerates its transformation towards a low-carbon and clean direction, hydrogen, as a key component of the future energy system, is increasingly becoming a core bottleneck restricting the construction and improvement of the hydrogen energy industry chain due to its sustainability of sources, efficiency of storage and transportation processes, and lack of flexibility.
[0003] In this context, Metal-Organic Framework Materials (MOFs), as an emerging class of porous crystalline materials that occupy an important position at the forefront of materials science, have demonstrated extraordinary application potential and scientific research value in the fields of gas molecule recognition and separation, efficient hydrogen storage, and catalytic reactions due to their ultra-high specific surface area, finely adjustable pore structure, and rich and diverse chemical composition. It is particularly noteworthy that the widespread unsaturated metal sites within MOFs not only provide abundant adsorption sites for hydrogen molecules, thereby achieving a high hydrogen storage density, but also serve as catalytic active centers, exhibiting unique catalytic performance and selectivity in various catalytic reaction systems such as photocatalysis and electrocatalysis. MOFs are considered to be ideal candidate materials in the field of photocatalytic hydrogen production due to their unique physicochemical properties, such as high specific surface area that promotes light absorption and contact with reactants, rich pore structure that facilitates gas diffusion, and structural adjustability that facilitates functional modification. However, despite the broad prospects, the practical application of MOFs in photocatalytic water splitting reactions still faces many challenges, mainly including insufficient oxidation potential of photogenerated holes, low carrier separation and transport efficiency, etc. These defects limit their ability to produce hydrogen without the addition of external sacrificial agents.
[0004] To overcome these obstacles, the design strategies for novel MOF-based composite materials are being actively explored. Core-shell MOF@MOF hybrid materials have attracted considerable attention due to their unique structural advantages. By finely regulating the chemical composition and spatial arrangement of the core-shell components, these materials not only achieve functional complementarity and enhancement, but also utilize the clear definition of the core-shell interface to promote the directional transport and efficient separation of electrons, significantly improving the charge transfer rate and quantum efficiency in photocatalytic reactions. Therefore, the development and application of core-shell MOF@MOF hybrid materials not only provides new ideas and solutions for photocatalytic hydrogen production technology, but also lays a solid material foundation for the sustainable development of hydrogen energy systems.
[0005] Currently, the mainstream strategy for constructing core-shell MOF@MOF composite materials focuses on the seed-induced growth mechanism, which uses the pre-synthesized MOF core as a template to guide and promote the directional growth of the subsequent shell MOF. Specifically, this strategy often requires complex surface modification of the core MOF to optimize the interaction interface between it and the shell MOF, thereby precisely controlling the growth direction of the shell MOF. On the other hand, self-assembly synthesis, as a potential alternative, aims to spontaneously form core-shell MOF@MOF composite materials with specific structures and functions through non-covalent interactions between molecules or between molecules and substrates. This method can not only effectively integrate multiple functional components and maintain the overall structural integrity of the material, but also exhibits high flexibility and design freedom. However, at the level of kinetic control, especially in the precise control of the thickness of the shell MOF, the self-assembly synthesis method still faces many technical difficulties, and further optimization of reaction conditions and synthesis strategies is needed.
[0006] In order to overcome the above challenges and further improve the performance of MOF-based photocatalysts, the use of built-in electric fields as the driving force for charge separation and transport has been explored. Among them, piezoelectric materials can produce polarization when subjected to mechanical stretching or strain, thereby forming a built-in electric field inside the material. This electric field can not only effectively inhibit the recombination of photogenerated electron-hole pairs and prolong the carrier lifetime, but also induce energy band bending at the solid-liquid interface, optimize the energy level matching of the catalytic reaction, and thus significantly improve the catalytic activity. The interfacial effect between the core MOF and the shell MOF, combined with the built-in electric field generated by the piezoelectric effect, jointly promotes the directional migration and effective separation of photogenerated charge carriers, injecting new vitality into the research of the emerging field of piezoelectric photocatalysis. Therefore, in-depth research on the piezoelectric photocatalytic mechanism of core-shell MOF@MOF composites is carried out to explore their application potential in energy conversion and storage, environmental purification and other fields. Summary of the Invention
[0007] In view of the defects and shortcomings of the existing technology, the present invention prepares a core-shell NH2-MIL-68@NH2-MIL-53 piezoelectric photocatalyst to achieve efficient piezoelectric-photocatalytic water splitting.
[0008] In order to achieve the above object of the invention, the specific technical solutions of the present invention are as follows:
[0009] (1) Indium nitrate and 2-aminoterephthalic acid were dissolved in N,N-dimethylformamide solvent and dispersed uniformly by ultrasonication. The resulting mixture was transferred to a polytetrafluoroethylene-lined autoclave for solvothermal reaction, thereby obtaining the product NH2-MIL-68(In).
[0010] (2) The NH2-MIL-68(In) and ferric nitrate obtained in the reaction of (1) are dissolved in N,N-dimethylformamide solvent and dispersed uniformly by ultrasonication; then a solvent thermal reaction is carried out, and the obtained product is filtered, washed with N,N-dimethylformamide solution and ethanol respectively, and placed in an oven to dry to obtain the target product.
[0011] In the present invention, the preparation method of NH2-MIL-68(In) comprises the following steps:
[0012] Indium nitrate and 2-aminoterephthalic acid are dissolved in 5-80 mL of N,N-dimethylformamide solution at a molar ratio of 1:0.8-1.2 and uniformly dispersed by ultrasonication; the resulting mixture is transferred to a 10-100 mL polytetrafluoroethylene-lined autoclave and heated at 80-200° C. for 2-48 hours; the precipitate is collected by centrifugal filtration and washed several times with N,N-dimethylformamide solution and anhydrous ethanol, and the washed precipitate is dried in an oven at 40-100° C. for 10-60 hours to obtain the product NH2-MIL-68(In).
[0013] In step (2) of the present invention, the preparation method of the NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction piezoelectric photocatalyst comprises the following steps:
[0014] NH2-MIL-68(In) and ferric nitrate are dissolved in 5-80 mL of N,N-dimethylformamide solvent at a molar ratio of 1:0.1-10 and dispersed evenly by ultrasonication. A solvothermal reaction is then performed, and the resulting product is filtered, washed with N,N-dimethylformamide solution and ethanol, respectively, and dried in an oven at 40-100°C for 10-60 hours to obtain the target product.
[0015] In step (2) of the present invention, the solvent-thermal reaction conditions of the NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction are: heating temperature of 80-200°C, reaction time of 12-144h; and the solvent is 5-80mL of N,N-dimethylformamide solution.
[0016] In addition, the present invention also provides an application of a core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) heterostructure prepared by the preparation method, which can achieve efficient piezoelectric-photocatalytic complete water splitting activity.
[0017] Furthermore, the core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst was ultrasonically dispersed in an aqueous solution, the solution was evacuated and nitrogen was introduced, and the catalytic reaction was carried out under the combined action of visible light and ultrasound.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) This invention proposes an innovative method for preparing MOF-based heterojunction piezoelectric photocatalysts. The core of this method is to finely control the Fe 3+ By adjusting the concentration of ions, the shell thickness of the NH2-MIL-53(Fe) catalyst can be precisely controlled, resulting in the in situ preparation of a series of NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction piezoelectric photocatalysts with different shell thicknesses. This preparation strategy not only simplifies the complexity of traditional catalyst synthesis but also endows the catalyst with the ability to maintain high catalytic activity and excellent stability through the synergistic action of photocatalysis and piezoelectric effects.
[0020] (2) At the structural design level, the present invention cleverly utilizes the inherent internal electric field characteristics of the asymmetric MOFs structure, which can form a significant polarization potential under specific conditions. This polarization potential, as a driving factor, greatly promotes the efficient transmission and effective separation of photogenerated charge carriers within the catalyst, reduces carrier recombination losses, and thus significantly improves carrier utilization and catalytic efficiency. This mechanism not only deepens the understanding of the photoelectric properties of asymmetric MOFs materials, but also provides new ideas and strategies for the development of high-performance photocatalytic water splitting technology.
[0021] (3) When subjected to the dual effects of light and mechanical stress, the NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst of the present invention can simultaneously utilize the advantages of photocatalysis and the piezoelectric effect to achieve efficient decomposition of water molecules, producing hydrogen and oxygen. Its high catalytic activity and high stability have been verified during continuous operation and long-term storage, demonstrating good practical application potential. Therefore, the present invention not only makes an important contribution to technological progress in the field of photocatalytic water splitting, but also opens up broad prospects for the future development and utilization of clean energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 X-ray diffraction spectra of NH2-MIL-68(In), NH2-MIL-53(Fe) and NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction piezoelectric photocatalysts with different molar ratios prepared in Examples 1-5.
[0023] Figure 2 This is a transmission electron microscope image of NH2-MIL-68(In) nanorods prepared in Example 1.
[0024] Figure 3This is a transmission electron microscope image of the core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction prepared in Example 3.
[0025] Figure 4 Bar graph a in the figure is the overall water splitting efficiency of the NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction piezoelectric photocatalyst prepared in Example 3; Figure 4 The bar graph b in FIG is the overall water splitting efficiency of the NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction piezoelectric photocatalyst prepared in Example 4; Figure 4 Bar graph c in FIG is the overall water splitting efficiency of the NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction piezoelectric photocatalyst prepared in Example 5.
[0026] Figure 5 This is a transmission electron microscope image of the core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction prepared in Example 4.
[0027] Figure 6 This is a transmission electron microscope image of the core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) heterojunction prepared in Example 5. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific implementation methods, but this should not be understood as the scope of the above-mentioned subject matter of the present invention being limited to the following embodiments.
[0029] Example 1:
[0030] A method for preparing NH2-MIL-68(In) comprises the following steps:
[0031] 1 mmol of indium nitrate and 1 mmol of 2-aminoterephthalic acid were dissolved in 10 mL of N, N-dimethylformamide solution and dispersed evenly by ultrasonication for 10 minutes. The mixture was then transferred to a 25 mL polytetrafluoroethylene-lined autoclave and reacted at a constant temperature of 125 ° C for 12 hours. The precipitate was collected by centrifugal filtration, washed several times with N, N-dimethylformamide and anhydrous ethanol, and then dried in an oven at 60 ° C for 24 hours. The obtained sample is NH2-MIL-68 (In). Its X-ray diffraction spectrum is as follows Figure 1 As shown by the middle curve a, its morphology is as follows Figure 2 shown.
[0032] Example 2:
[0033] A method for preparing NH2-MIL-53(Fe) comprises the following steps:
[0034] 1 mmol of ferric nitrate and 1 mmol of 2-aminoterephthalic acid were dissolved in 10 mL of N, N-dimethylformamide solution and dispersed evenly by ultrasonication for 10 minutes. The mixture was then transferred to a 25 mL polytetrafluoroethylene-lined autoclave and reacted at a constant temperature of 125 ° C for 5 hours. The precipitate was collected by centrifugal filtration, washed several times with N, N-dimethylformamide and anhydrous ethanol, and then dried in an oven at 60 ° C for 24 hours. The obtained sample is NH2-MIL-53 (Fe). Its X-ray diffraction spectrum is as follows Figure 1 As shown in the middle curve b.
[0035] Example 3:
[0036] A method for preparing a core-shell NH2-MIL-68@NH2-MIL-53 piezoelectric photocatalyst comprises the following steps:
[0037] Take 1 mmol of NH2-MIL-66(In) synthesized in Example 1 and 0.5 mmol of ferric nitrate and dissolve them in 20 mL of N,N-dimethylformamide solution, and disperse the mixed solution evenly by ultrasonication for 10 minutes. The mixture was sealed in a 50 mL polytetrafluoroethylene-lined high-pressure reactor and reacted at a constant temperature of 160°C for 24 hours. The precipitate was collected by centrifugation, washed several times with N,N-dimethylformamide and anhydrous ethanol, and further dried in an oven at 60°C for 12 hours. The final sample obtained is NH2-MIL-68(In)@NH2-MIL-53(Fe). Its X-ray diffraction spectrum is shown below. Figure 1 As shown by the curve c in the middle, its morphology is as follows Figure 3 shown.
[0038] The following is an application example of using the catalyst prepared in this embodiment for piezoelectric-photocatalytic overall water splitting:
[0039] 5 mg of the above-mentioned NH2-MIL-68@NH2-MIL-53 piezoelectric photocatalyst was added to a photocatalytic reactor filled with 50 ml of deionized water. The reactor was cooled with circulating water at -10 °C, a xenon lamp was used as the light source, and a cutoff filter with a λ≧420 nm was used. The piezoelectric-photocatalytic overall water splitting test was carried out under the conditions of an ultrasonic machine frequency of 40 kHz and a power of 100 W. The piezoelectric-photocatalytic hydrogen and oxygen production were tested by gas chromatography. The calculated results are shown in Figure 4 As shown in the middle curve a.
[0040] Example 4:
[0041] The same parts of this embodiment as those of the third embodiment are not described in detail. The differences are as follows:
[0042] The molar amount of ferric nitrate is 1 mmol, and its X-ray diffraction spectrum is as follows: Figure 1 As shown by the middle curve d, its morphology is as follows Figure 4 shown.
[0043] The prepared NH2-MIL-68@NH2-MIL-53 was subjected to piezoelectric-photocatalytic experiments under the same conditions as in Example 3. The results of the piezoelectric-photocatalytic hydrogen and oxygen production are shown in Figure 4 As shown in the middle curve b.
[0044] Embodiment 5:
[0045] The same parts of this embodiment as those of the third embodiment are not described in detail. The differences are as follows:
[0046] The molar amount of ferric nitrate is 2mmol, and its X-ray diffraction spectrum is as follows: Figure 1 As shown by the middle curve e, its morphology is as follows Figure 5 shown.
[0047] The prepared NH2-MIL-68@NH2-MIL-53 was subjected to piezoelectric-photocatalytic experiments under the same conditions as in Example 3. The results of the piezoelectric-photocatalytic hydrogen and oxygen production are shown in Figure 4 As shown in the middle curve c.
[0048] The above contents are merely examples of the present invention. Those skilled in the art may modify, supplement or replace the described embodiments without departing from the scope of the present invention, and all such modifications, additions or replacements shall be deemed to fall within the scope of protection of the present invention.
Claims
1. An NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and a preparation method thereof, characterized in that: The preparation method comprises the following steps: (1) Indium nitrate and 2-aminoterephthalic acid were dissolved in N,N-dimethylformamide solvent and dispersed uniformly by ultrasonication. The resulting mixture was transferred to a polytetrafluoroethylene-lined autoclave for solvothermal reaction, thereby obtaining the product NH2-MIL-68(In). (2) The NH2-MIL-68(In) and ferric nitrate obtained in the reaction of (1) are dissolved in N,N-dimethylformamide solvent and dispersed uniformly by ultrasonication; then a solvent thermal reaction is carried out, and the obtained product is filtered, washed with N,N-dimethylformamide solution and ethanol respectively, and placed in an oven to dry to obtain the target product.
2. The NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and its preparation method according to claim 1, characterized in that: In step (1), the molar ratio of indium nitrate to 2-aminoterephthalic acid is 1:0.8-1.
2.
3. A core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and a preparation method thereof according to claim 1, characterized in that: In step (1), the volume of the polytetrafluoroethylene liner is 10-100 mL, and the volume of the N,N-dimethylformamide solvent is 5-80 mL.
4. A core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and a preparation method thereof according to claim 1, characterized in that: In step (1), the solvent thermal reaction temperature is 80-200° C., and the reaction time is 2-48 hours.
5. A core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and a preparation method thereof according to claim 1, characterized in that: In step (2), the molar ratio of NH2-MIL-68(In) to ferric nitrate is 1:0.1-10.
6. A core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and a preparation method thereof according to claim 1, characterized in that: In step (2), the volume of the polytetrafluoroethylene liner is 10-100 mL, and the volume of the N,N-dimethylformamide solvent is 5-80 mL.
7. A core-shell NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst and a preparation method thereof according to claim 1, characterized in that: In step (2), the solvent thermal reaction temperature is 60-200° C., and the reaction time is 12-144 h.
8. The use of the NH2-MIL-68(In)@NH2-MIL-53(Fe) heterostructure according to claim 1, characterized in that: This heterostructure can achieve efficient piezoelectric-photocatalytic water splitting activity.
9. The use according to claim 8, characterized in that The method is as follows: ultrasonically disperse the NH2-MIL-68(In)@NH2-MIL-53(Fe) piezoelectric photocatalyst described in claim 1 in an aqueous solution, evacuate the solution and introduce nitrogen, and carry out a catalytic reaction under the combined action of visible light and ultrasound.